The Implementation of Interactive Google Slides–Based Learning Media in Enhancing Students’ Learning Participation at Nurud Dzolam Alassumur Islamic Elementary School - Riana Imroatul Fitriah; Ainur Rofiq Sofa (DAAR EL-MAKRIFAH: Journal of Islamic Religious Education, 2025)
The integration of digital learning media has become increasingly important in supporting active learning at the elementary school level. Student participation is a key indicator of effective learning, particularly in Madrasah Ibtidaiyah, where students require visually supported and interactive instruction. This study aims to examine the use of interactive Google Slides–based learning media in improving students’ learning participation at Nurud Dzolam Alassumur Islamic Elementary School, Kraksaan. This study employed a qualitative descriptive approach. Data were collected through classroom observations, in-depth interviews, and documentation involving the school principal, the vice principal for curriculum affairs, the Islamic Education (PAI) teacher, and students. The data were analyzed thematically to explore the implementation process, challenges encountered, and the impact of interactive Google Slides on students’ learning participation. The findings indicate that interactive Google Slides effectively create an engaging and student-centered learning environment. The use of visual elements, animations, and interactive questions increased students’ attention, enthusiasm, and active participation during classroom activities. Students became more confident in responding to questions, including those who were previously passive. However, challenges were identified related to preparation time and limited technological facilities.This study concludes that interactive Google Slides–based learning media are effective in enhancing students’ learning participation at the Madrasah Ibtidaiyah level and can serve as a practical instructional strategy to support active learning in Islamic elementary education.